The Effect of Integrity, Professionalism, and Innovation on Service Performance - Suparjo; Corry Yohana; Ma'ruf Akbar (Journal of Business and Behavioural Entrepreneurship, 2020)
This study aims to analyze the influence of Integrity, Professionalism, and Innovation in order to encourage the achievement of good service performance. This study involved 207 people from 384 employees at the State Treasury Service Office in the Regional Office of the Directorate General of Treasury, Jakarta Province. The seven KPPNs were chosen because they have the same service user characteristics as other KPPNs and can represent KPPNs throughout Indonesia. Nationally, in terms of the budget managed and the number of work units served, more than half are served by the seven KPPNs. The average amount of the state budget managed by the seven KPPNs is 75.5% of all funds nationally. The technical analysis used is descriptive statistics and inferential statistics, with hypothesis testing tools using Path Analysis. The results of the study show that Integrity has a positive and significant effect on Service Performance, Professionalism has a positive and significant effect on Service Performance, Innovation has a positive and significant effect on Service Performance, Integrity positive and significant effect on Innovation, Professionalism positive and significant effect on Innovation and Integrity, Professionalism, and Innovation together have a positive and significant effect on Service Performance. This research provides evidence that Integrity, Professionalism, and Innovation as elements of the Ministry of Finance Values ​​can create a bureaucracy that has good public service performance, so it needs to be continuously socialized and internalized to all employees of the Ministry of Finance.